AN ASSESSMENT OF THE EFFECT OF RAIN CHARACTERISTICS AGAINSTS THE VOLUME OF WATER FLOW AND THE WEIGHT OF SUSPENSION IN KARST AREA - Marcellinus Mandira Budi Utomo; Hatma Suryatmojo; Sri Astuti Soedjoko (Pusbindiklat - LIPI, 2012)
The watershed management needs data of hydrology circulation, e.g. volume of water flow and weight ofsuspension. Rain is a main control for hydrology circulation. Rain characteristics need to be assessed for their effectagainst hydrology circulation. This research was aimed to assess the effect of rain characteristics and to createan equation of volume of water flow and weight of suspension in karst area. A combination method of explorationand statistic calculation was used in this research. Parameters of volume of water flow and weight of suspensionwas measured at several different of water levels. The data were analyzed to assess the rain characteristics thatinfluenced hydrology circulation. The result showed that 30 minutes maximum intensity (I 30’) affected the volumeof water flow and weight of suspension. The functions raised from this research were V = 563.646 (I 30’ )–644.063and W = 59.660 (I 30’ )–209.758.